2009
DOI: 10.3748/wjg.15.1985
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in adults: Clinical characteristics, diagnosis and operative strategies

Abstract: Adult intussusception is an unusual and challenging condition and is a preoperative diagnostic problem. Treatment usually requires resection of the involved bowel segment. Reduction can be attempted in small-bowel intussusception if the segment involved is viable or malignancy is not suspected; however, a more careful approach is recommended in colonic intussusception because of a significantly higher coexistence of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
261
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(282 citation statements)
references
References 27 publications
9
261
0
12
Order By: Relevance
“…7 This was the finding in our case; we performed a simple reduction only and this fact is supported by several studies. 6 The aetiology is a malignancy in most of the cases of large bowel intussusception as opposed to small bowel intussusception.…”
Section: Figure 1: the Ileo-ileal Intussusceptionssupporting
confidence: 74%
“…7 This was the finding in our case; we performed a simple reduction only and this fact is supported by several studies. 6 The aetiology is a malignancy in most of the cases of large bowel intussusception as opposed to small bowel intussusception.…”
Section: Figure 1: the Ileo-ileal Intussusceptionssupporting
confidence: 74%
“…The group also carried out risk analysis and found history of previous malignancy, mass on CT and age over 60 to be associated with presence of a lead point in small bowel intussusceptions; this may have implications in optimising the incidence of bowel resection. Yakan et al reported 20 cases out of which 17 involved small bowel with 2 showing no demonstrable pathology [8]. Although resection may be performed after partial reduction, either by traction or hydrostatic means [9], this may result in inadvertent perforation.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions seem to lack a malignant potential and recurrence of the polyps has been reported only once [9]. Conventional abdominal radiography may show dilated bowel loops.…”
Section: Discussionmentioning
confidence: 99%